A sandwich-type silicon composite graphite negative electrode material and lithium-ion battery

By using a combination of sandwich-type silicon composite graphite structure and carbon layer in the negative electrode material of lithium-ion batteries, the problems of silicon volume changes and SEI film generation during charging and discharging of lithium-ion batteries are solved, and high energy density and good cycle retention rate are achieved.

CN118630196BActive Publication Date: 2025-04-01NINGBO HANGCHANG METAL MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411090388.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-04-01
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

During the charging and discharging process, the volume changes greatly due to the alloying and dealloyment of silicon, and the SEI films are frequently generated and ruptured, resulting in a decrease in Coulomb efficiency and capacity attenuation, and poor circulation performance.

Method used

Sandwich-type silicon composite graphite negative electrode material is used, and the carbon layer is combined with a nano-silicon-graphite-nano-silicon structure and a carbon layer. The carbon layer includes hard carbon and amorphous carbon. The hard carbon is made of carbonized by dispersant. The amorphous carbon is generated by CVD in situ coating. The carbon layer not only relieves volume expansion, but also avoids direct contact between the nano-silicon and the electrolyte.

Benefits of technology

It significantly improves the conductivity and energy density of lithium-ion batteries, improves the cycle retention and rate performance, reduces the generation and rupture of SEI films, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118630196B_ABST
    Figure CN118630196B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium-ion battery materials, and relates to a sandwich-type silicon composite graphite negative electrode material and a lithium-ion battery. The present invention discloses a sandwich-type silicon composite graphite negative electrode material, which uses a nano-silicon-graphite-nano-silicon structure as a substrate, and a carbon layer is loaded on the surface of the substrate, and the carbon layer includes hard carbon and amorphous carbon; the amorphous carbon is loaded on the outer surface of the hard carbon, and part of the amorphous carbon is filled in the pores of the hard carbon. The present invention also discloses a lithium-ion battery based on the sandwich-type silicon composite graphite negative electrode material, and the lithium-ion battery has good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials and relates to a sandwich-type silicon composite graphite negative electrode material and a lithium ion battery. Background Art

[0002] Lithium-ion battery is an electrochemical energy storage device that can be reversibly charged and discharged, and has the advantages of long service life, high energy density, and wide operating temperature range. As an important component of lithium-ion batteries, negative electrode materials have a crucial impact on the cycle life and energy density of lithium-ion batteries.

[0003] However, the energy density of graphite anodes widely used in commercial lithium-ion batteries is close to the theoretical upper limit (372 mAh g -1 ), through simulation, when the negative electrode material capacity does not exceed 1200 mAh g -1 In this case, improving the capacity of existing negative electrode materials still makes a significant contribution to the energy density of the entire battery.

[0004] Silicon materials have high theoretical capacity (4200 mAh g -1 ), low lithium insertion and extraction potential (~0.4V vs. Li / Li + ), environmentally friendly, and abundant reserves, and is considered to be the next generation of high-energy density lithium-ion battery negative electrode materials that are most likely to be industrialized. However, silicon as a negative electrode material for lithium-ion batteries also has defects that cannot be ignored: as charging and discharging proceed, the alloying and dealloying of silicon causes the material volume change rate to be as high as 300%, the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode material continues to generate and crack, consuming active lithium to cause a decrease in coulomb efficiency, and the particle cracking and pulverization causes a sharp decrease in capacity attenuation and cycle performance.

[0005] At present, the effective means to alleviate the defects of silicon materials to a certain extent is to compound the silicon source with carbon materials, which can effectively improve the conductivity, volume expansion, cycle stability, etc. of silicon-based negative electrode materials. The existing silicon-carbon composite materials on the market have the disadvantages of high preparation cost and low first-cycle coulomb efficiency. Therefore, it is urgent to develop a silicon-carbon negative electrode material with simple preparation method, high first-cycle coulomb efficiency and excellent electrochemical performance. Summary of the invention

[0006] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a sandwich-type silicon composite graphite negative electrode material with a self-assembled structure, with a nano-silicon-graphite-nano-silicon structure as a substrate, a carbon layer loaded on the surface of the substrate, and the carbon layer including hard carbon and amorphous carbon; the hard carbon obtained by cracking the carbon source and the amorphous carbon obtained by CVD in-situ coating firmly adhere the nano-silicon to the graphite surface, effectively blocking the direct contact between the electrolyte and the nano-silicon, thereby improving the performance of the lithium-ion battery.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A sandwich-type silicon composite graphite negative electrode material has a nano-silicon-graphite-nano-silicon structure as a substrate, a carbon layer is loaded on the surface of the substrate, and the carbon layer includes hard carbon and amorphous carbon; the amorphous carbon is loaded on the outer surface of the hard carbon and filled in the pores of the hard carbon.

[0009] The outer surface carbon layer of the sandwich-type silicon composite graphite negative electrode material of the present invention includes two components, and the carbon layer can alleviate the volume expansion of silicon during alloying and dealloying; the amorphous carbon obtained by CVD in-situ coating is filled in the hard carbon pores, which reduces the specific surface area and also avoids direct contact between nano-silicon and electrolyte to generate a large amount of SEI film to deplete the electrolyte.

[0010] Preferably, the average size of the nano-silicon is 30-80 nm.

[0011] Preferably, the average size of the graphite is 5-10 μm.

[0012] Preferably, the graphite is in layered form.

[0013] Preferably, the graphite is artificial graphite.

[0014] Preferably, the average thickness of the carbon layer is 300-2000 nm.

[0015] If the carbon layer is too thick, the electron ion transmission distance will be too long, which will affect the lithium extraction of the sandwich silicon composite graphite negative electrode material and reduce the capacity of the sandwich silicon composite graphite negative electrode material; if the carbon layer is too thin, it will not provide effective buffering during the process of nano-silicon alloying and dealloying. When the sandwich silicon composite graphite negative electrode material is applied to the pole piece, an overly thick carbon layer will inevitably increase the particle size of the material, resulting in large particles on the surface of the pole piece during coating, and will increase the cost of material preparation.

[0016] Preferably, the hard carbon is obtained by carbonizing a dispersant.

[0017] Preferably, the amorphous carbon is generated by in-situ coating of a carbon source gas via CVD.

[0018] More preferably, the carbon source gas is a mixture of one or more of methane, ethylene, acetylene and argon.

[0019] Preferably, the sandwich-type silicon composite graphite negative electrode material is prepared by shearing and emulsifying nano-silicon powder and graphite in a dispersion, followed by spray drying, carbonization under an inert gas, and CVD in-situ coating under a carbon source gas.

[0020] Further preferably, the dispersion is prepared by adding a dispersant to a dispersion medium; the dispersant is polyvinyl pyrrolidone; and the dispersion medium is one or both of anhydrous ethanol and water.

[0021] A method for preparing a sandwich-type silicon composite graphite negative electrode material comprises:

[0022] (1) Adding a dispersant to a dispersion medium to obtain a dispersion;

[0023] (2) adding nano-silicon powder to the dispersion liquid and dispersing it by shearing and emulsification, and then adding graphite and dispersing it by shearing and emulsification to obtain a suspension;

[0024] (3) spray drying the suspension to obtain composite particles coated with a dispersant;

[0025] (4) placing the composite particles coated with the dispersant in an inert gas for carbonization to obtain a precursor;

[0026] (5) Placing the precursor in a carbon source gas for in-situ CVD coating.

[0027] Preferably, the dispersant in (1) is polyvinyl pyrrolidone; and the dispersion medium is one or both of anhydrous ethanol and water.

[0028] Preferably, the solid content of the dispersion in (1) is 1-20%.

[0029] Preferably, the mass ratio of nano-silicon powder to graphite in the suspension in (2) is 1:(3-20).

[0030] Preferably, the mass ratio of the dispersant to the graphite in the suspension of (2) is 1:(3-20).

[0031] Preferably, the shear emulsification speed in (2) is 3000-6000 rpm, and the shear emulsification time is 20-60 min.

[0032] Preferably, the spray drying temperature in (3) is 90-200° C., and the atomizing disk rotation speed is 15000-25000 rpm.

[0033] Preferably, the carbonization temperature in (4) is 850-1100°C, and the holding time is 1-6 h.

[0034] If the carbonization temperature is low, the dispersant cannot be carbonized into hard carbon, and the incompletely carbonized dispersant affects the conductive properties of the material; if the insulation time is short, incomplete carbonization will result.

[0035] Preferably, the inert gas in (4) is one of nitrogen, argon, and a hydrogen-argon mixed gas (5% hydrogen), and the inert gas flow rate is 200-500 sccm.

[0036] Preferably, the carbon source gas in (5) is a mixture of one or more of methane, ethylene, acetylene and argon.

[0037] More preferably, the flow rates of methane and ethylene are 0-200 sccm, the flow rate of acetylene is 200-600 sccm, and the flow rate of argon is 300-600 sccm.

[0038] Preferably, the CVD in-situ coating temperature in (5) is 850-1000°C, the heating rate is 1-20°C / min, and the holding time is 1-12 h.

[0039] More preferably, the CVD in-situ coating temperature in (5) is 950-1000°C, the heating rate is 5-10°C / min, and the holding time is 1-6 h.

[0040] If the coating temperature is too low, the carbon source gas cannot be cracked to generate amorphous carbon. If the insulation time is too short, the coating layer will not be fully formed and the structural consistency will be poor.

[0041] If the composite particles coated with the dispersant in (3) are directly placed in a CVD furnace for CVD in-situ coating, the dispersant will decompose / carbonize during the heating process, resulting in continuous gas generation / cracking of long-chain polymers at the CVD kinetic active sites on the substrate surface, making it impossible for the carbon source gas to be effectively deposited on the substrate surface, thereby failing to form amorphous carbon.

[0042] A lithium-ion battery negative electrode plate comprises a sandwich-type silicon composite graphite negative electrode material.

[0043] Preferably, the preparation method of the negative electrode sheet of a lithium-ion battery comprises: uniformly mixing a sandwich-type silicon composite graphite negative electrode material, a conductive agent and a binder, coating the mixture on a current collector, vacuum drying the mixture and then cutting the mixture.

[0044] More preferably, the mass ratio of the sandwich-type silicon composite graphite negative electrode material, the conductive agent and the binder is (7-9): (0.5-2.0): (0.5-2.0).

[0045] A lithium-ion battery comprises a negative electrode plate of the lithium-ion battery.

[0046] Preferably, the lithium-ion battery is assembled from a lithium-ion battery negative electrode sheet, a metal lithium positive electrode sheet, and an electrolyte.

[0047] More preferably, the electrolyte is 1 mol / L LiPF6 / DMC:EC (V:V=7:3) containing 5% FEC electrolyte additive. Beneficial Effects

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] 1. The present invention adopts a self-assembly method to prepare a sandwich-type silicon composite graphite negative electrode material, so that nano-silicon and graphite are spontaneously assembled into an ordered structure to form a substrate of nano-silicon-graphite-nano-silicon structure;

[0050] 2. The sandwich-type silicon composite graphite negative electrode material of the present invention has a multi-layered structure, with graphite as a support, nano-silicon located on the graphite surface, forming a substrate of nano-silicon-graphite-nano-silicon structure, and a carbon layer is loaded on the outside of the nano-silicon, forming a sandwich-type structure as a whole; and the hard carbon in the carbon layer is connected to the nano-silicon, part of the amorphous carbon is loaded on the outer surface of the hard carbon, and the remaining part of the amorphous carbon is filled in the pores of the hard carbon;

[0051] 3. In the sandwich-type silicon composite graphite negative electrode material of the present invention, nano-silicon provides capacity, and graphite and carbon layers provide conductivity; the outer carbon layer not only prevents the nano-silicon particles from directly contacting the electrolyte to generate a large amount of SEI film to deplete the electrolyte, but also alleviates the volume expansion to a certain extent; at the same time, the nano-silicon is tightly attached to the graphite, and will not break and detach as the cycle proceeds;

[0052] 4. In the preparation process of the sandwich-type silicon composite graphite negative electrode material of the present invention, the substrate of the nano-silicon-graphite-nano-silicon structure is carbonized and CVD in-situ coated; the dispersant loaded on the surface of the substrate during the carbonization process is dehydrated, cracked, and carbonized, and the surface of the substrate is covered with hard carbon to form a porous structure; in the CVD in-situ coating process, the carbon source gas is cracked at high temperature, and the amorphous carbon obtained by the cracking is deposited on the active sites of the substrate, thereby forming a uniform and dense amorphous carbon layer, and part of the amorphous carbon is filled in the hard carbon pores;

[0053] 5. The conductivity of the sandwich-type silicon composite graphite negative electrode material of the present invention is significantly improved compared with that of nano silicon powder, which fills the defects of insufficient energy density and low cycle retention rate of silicon-carbon negative electrode materials in the current field of lithium-ion battery negative electrode materials;

[0054] 6. The lithium-ion battery assembled with the negative electrode sheets made of the sandwich-type silicon composite graphite negative electrode material of the present invention has good energy density and cycle retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a scanning electron microscope (SEM) photograph of the sandwich-type silicon composite graphite negative electrode material in Example 1 of the present invention.

[0056] Figure 2 This is a rate charge and discharge curve diagram of the lithium ion battery in Application Example 1 of the present invention.

[0057] Figure 3This is a cycle curve diagram of the lithium-ion battery in Application Example 1 of the present invention.

[0058] Figure 4 This is a rate charge and discharge curve diagram of the lithium ion battery in comparative example 2 of the present invention.

[0059] Figure 5 This is a cycle curve diagram of the lithium ion battery in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0060] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0061] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.

[0062] The sandwich-type silicon composite graphite negative electrode material of the present invention uses nano-silicon-graphite-nano-silicon structure as substrate, and the surface of the substrate is loaded with a carbon layer, the carbon layer includes hard carbon and amorphous carbon; the amorphous carbon is loaded on the outer surface of the hard carbon, and part of the amorphous carbon is filled in the pores of the hard carbon.

[0063] The carbon layer in the sandwich-type silicon composite graphite negative electrode material of the present invention not only prevents the nano-silicon particles from directly contacting the electrolyte to generate a large amount of SEI film to deplete the electrolyte, but also alleviates the volume expansion to a certain extent; at the same time, the nano-silicon is also tightly attached to the graphite, and will not break and detach with the progress of the cycle. Therefore, the lithium-ion battery assembled by making the sandwich-type silicon composite graphite negative electrode material into a negative electrode material has good energy density, cycle retention rate, and rate performance. Example 1

[0064] Preparation of sandwich-type silicon composite graphite negative electrode material:

[0065] (1) First, add 300 g of polyvinyl pyrrolidone into 24 kg of anhydrous ethanol and wait for it to fully dissolve to obtain a dispersion;

[0066] (2) Add 300 g of nano-silicon powder with a D50 of 50 nm to the dispersion, shear emulsify at 4200 rpm for 10 min, then add 2.4 kg of artificial graphite with a D50 of 8 μm, and shear emulsify at 4200 rpm for 20 min to obtain a uniformly dispersed suspension;

[0067] (3) The suspension was spray dried, mechanical stirring was required during feeding, and a peristaltic pump was used for feeding at the same time. The spray drying temperature was 100 °C, the atomizing disk speed was 18,000 rpm, the peristaltic pump feeding rate was 20 Hz, and the mechanical stirring rate was 200 rpm to obtain composite particles coated with a dispersant.

[0068] (4) The composite particles coated with the dispersant were placed in a rotary kiln for carbonization. The rotary kiln speed was 20 rpm. Argon was used as the inert gas with a flow rate of 500 sccm. The carbonization temperature was 900 °C and the heating rate was 10 °C / min. After being kept at 900 °C for 2 h, the precursor was naturally cooled to obtain the precursor.

[0069] (5) The precursor was coated in situ by CVD, the CVD furnace speed was 10 rpm, the CVD temperature was 950 °C, 450 sccm of Ar, 350 sccm of C2H2, and 100 sccm of CH4 were introduced, the heating rate was 5 °C / min, and the temperature was kept for 2 h; a sandwich-type silicon composite graphite negative electrode material was obtained.

[0070] The sandwich-type silicon composite graphite negative electrode material prepared in this embodiment uses graphite as a support, and its surface is loaded with nano-silicon to form a substrate of nano-silicon-graphite-nano-silicon structure. A carbon layer is loaded on the surface of the substrate, and the carbon layer includes hard carbon and amorphous carbon. Figure 1 This is a scanning electron microscope image of the sandwich-type silicon composite graphite negative electrode material prepared in this embodiment. Example 2

[0071] Preparation of sandwich-type silicon composite graphite negative electrode material:

[0072] (1) First, add 300 g of polyvinyl pyrrolidone into 24 kg of anhydrous ethanol and wait for it to fully dissolve to obtain a dispersion;

[0073] (2) Add 300 g of nano-silicon powder with a D50 of 80 nm to the dispersion, shear emulsify at 4200 rpm for 10 min, then add 2.4 kg of artificial graphite with a D50 of 8 μm, and shear emulsify at 4200 rpm for 20 min to obtain a uniformly dispersed suspension;

[0074] (3) The suspension was spray dried, mechanical stirring was required during feeding, and a peristaltic pump was used for feeding at the same time. The spray drying temperature was 100 °C, the atomizing disk speed was 18,000 rpm, the peristaltic pump feeding rate was 20 Hz, and the mechanical stirring rate was 200 rpm to obtain composite particles coated with a dispersant.

[0075] (4) The composite particles coated with the dispersant were placed in a rotary kiln for carbonization. The rotary kiln speed was 20 rpm. Argon was used as the inert gas with a flow rate of 500 sccm. The carbonization temperature was 900 °C and the heating rate was 10 °C / min. After being kept at 900 °C for 2 h, the precursor was naturally cooled to obtain the precursor.

[0076] (5) The precursor was coated in situ by CVD, the CVD furnace speed was 10 rpm, the CVD temperature was 950 °C, 450 sccm of Ar, 350 sccm of C2H2, and 100 sccm of CH4 were introduced, the heating rate was 5 °C / min, and the temperature was kept for 2 h; a sandwich-type silicon composite graphite negative electrode material was obtained. Example 3

[0077] Preparation of sandwich-type silicon composite graphite negative electrode material:

[0078] (1) First, add 300 g of polyvinyl pyrrolidone into 30 kg of ultrapure water and wait for it to fully dissolve to obtain a dispersion;

[0079] (2) Add 300 g of nano-silicon powder with a D50 of 50 nm to the dispersion, shear emulsify at 4200 rpm for 10 min, then add 2.4 kg of artificial graphite with a D50 of 8 μm, and shear emulsify at 4200 rpm for 20 min to obtain a uniformly dispersed suspension;

[0080] (3) The suspension was spray dried, mechanical stirring was required during feeding, and a peristaltic pump was used for feeding at the same time. The spray drying temperature was 150 °C, the atomizing disk speed was 18000 rpm, the peristaltic pump feeding rate was 20 Hz, and the mechanical stirring rate was 200 rpm to obtain composite particles coated with a dispersant.

[0081] (4) The composite particles coated with the dispersant were placed in a rotary kiln for carbonization. The rotary kiln speed was 20 rpm. Argon was used as the inert gas with a flow rate of 500 sccm. The carbonization temperature was 900 °C and the heating rate was 10 °C / min. After being kept at 900 °C for 2 h, the precursor was naturally cooled to obtain the precursor.

[0082] (5) The precursor was coated in situ by CVD, the CVD furnace speed was 10 rpm, the CVD temperature was 950 °C, 450 sccm of Ar, 350 sccm of C2H2, and 100 sccm of CH4 were introduced, the heating rate was 5 °C / min, and the temperature was kept for 2 h; a sandwich-type silicon composite graphite negative electrode material was obtained. Example 4

[0083] Preparation of sandwich-type silicon composite graphite negative electrode material:

[0084] (1) First, add 300 g of polyvinyl pyrrolidone into 24 kg of anhydrous ethanol and wait for it to fully dissolve to obtain a dispersion;

[0085] (2) Add 300 g of nano-silicon powder with a D50 of 50 nm to the dispersion, shear emulsify at 4200 rpm for 10 min, then add 2.4 kg of artificial graphite with a D50 of 8 μm, and shear emulsify at 4200 rpm for 20 min to obtain a uniformly dispersed suspension;

[0086] (3) The suspension was spray dried, mechanical stirring was required during feeding, and a peristaltic pump was used for feeding at the same time. The spray drying temperature was 100 °C, the atomizing disk speed was 18,000 rpm, the peristaltic pump feeding rate was 20 Hz, and the mechanical stirring rate was 200 rpm to obtain composite particles coated with a dispersant.

[0087] (4) The composite particles coated with the dispersant were placed in a rotary kiln for carbonization. The rotary kiln speed was 20 rpm. Argon was used as the inert gas with a flow rate of 500 sccm. The carbonization temperature was 900 °C and the heating rate was 10 °C / min. After being kept at 900 °C for 2 h, the precursor was naturally cooled to obtain the precursor.

[0088] (5) The precursor was coated in situ by CVD, the CVD furnace speed was 10 rpm, the CVD temperature was 950 °C, 450 sccm of Ar, 200 sccm of C2H2, and 200 sccm of CH4 were introduced, the heating rate was 5 °C / min, and the temperature was kept for 2 h; a sandwich-type silicon composite graphite negative electrode material was obtained. Comparative Example 1

[0089] Preparation of negative electrode materials:

[0090] (1) First, add 300 g of polyvinyl pyrrolidone into 24 kg of anhydrous ethanol and wait for it to fully dissolve to obtain a dispersion;

[0091] (2) Add 300 g of nano-silicon powder with a D50 of 50 nm to the dispersion, shear emulsify at 4200 rpm for 10 min, then add 2.4 kg of artificial graphite with a D50 of 8 μm, and shear emulsify at 4200 rpm for 20 min to obtain a uniformly dispersed suspension;

[0092] (3) The suspension was spray dried, mechanical stirring was required during feeding, and a peristaltic pump was used for feeding at the same time. The spray drying temperature was 100 °C, the atomizing disk speed was 18,000 rpm, the peristaltic pump feeding rate was 20 Hz, and the mechanical stirring rate was 200 rpm to obtain composite particles coated with a dispersant.

[0093] (4) The composite particles coated with the dispersant were placed in a rotary kiln for carbonization. The rotary kiln speed was 20 rpm. Argon was used as the inert gas with a flow rate of 500 sccm. The carbonization temperature was 900 °C and the heating rate was 10 °C / min. After keeping at 900 °C for 2 h, the mixture was naturally cooled to obtain the negative electrode material.

[0094] The negative electrode material prepared in this comparative example uses graphite as a support, and its surface is loaded with a nano-silicon particle layer and hard carbon in sequence; since there is no amorphous carbon brought by CVD in-situ coating to fill the pores brought by the pyrolysis of organic hard carbon, the material has an excessively large specific surface area, and part of the nano-silicon powder is in direct contact with the electrolyte, affecting the electrochemical performance. Comparative Example 2

[0095] Preparation of negative electrode materials:

[0096] (1) First, add 300 g of polyvinyl pyrrolidone into 24 kg of anhydrous ethanol and wait for it to fully dissolve to obtain a dispersion;

[0097] (2) Add 300 g of nano-silicon powder with a D50 of 50 nm to the dispersion, shear emulsify at 4200 rpm for 10 min, then add 2.4 kg of artificial graphite with a D50 of 8 μm, and shear emulsify at 4200 rpm for 20 min to obtain a uniformly dispersed suspension;

[0098] (3) The suspension was spray dried, mechanical stirring was required during feeding, and a peristaltic pump was used for feeding at the same time. The spray drying temperature was 100 °C, the atomizing disk speed was 18,000 rpm, the peristaltic pump feeding rate was 20 Hz, and the mechanical stirring rate was 200 rpm to obtain composite particles coated with a dispersant.

[0099] (4) The composite particles coated with the dispersant were placed in a rotary kiln for carbonization. The rotary kiln speed was 20 rpm. Argon was used as the inert gas with a flow rate of 500 sccm. The carbonization temperature was 900 °C and the heating rate was 10 °C / min. After keeping at 900 °C for 4 h, the mixture was naturally cooled to obtain the negative electrode material.

[0100] Application Example 1

[0101] Preparation of negative electrode sheet:

[0102] A sandwich-type silicon composite graphite negative electrode material, a conductive agent (carbon black) and a binder (PVDF) in a mass ratio of 8:1:1 were mixed evenly and coated on the current collector. After vacuum drying at 60°C for 12 hours, the negative electrode sheets were cut.

[0103] Preparation of lithium-ion batteries:

[0104] The above-mentioned negative electrode was used as the electrode to be tested, metallic lithium was used as the reference electrode, and 1 mol / L LiPF6 / DMC:EC (V:V=7:3) containing 5% FEC electrolyte additive was used as the electrolyte; a lithium-ion button half-cell was assembled in a glove box filled with argon.

[0105] Carry out charge and discharge test, the charge and discharge voltage range is 0.01~1.5V (vs.Li + / Li), the test temperature is 30 ℃.

[0106] pass Figure 2 , 3 It can be seen that the discharge capacity of the lithium-ion battery in this application example is 560.6 mAh g -1 ; After high-current charge and discharge, the capacity can be restored to 95% of the initial capacity, showing excellent rate characteristics; under 0.2 C current cycling, the capacity retention rate of 50 cycles is 96.31%, showing excellent cycle characteristics.

[0107] Application Examples 2~4

[0108] The sandwich-type silicon composite graphite negative electrode materials in Examples 2 to 4 were made into negative electrode sheets according to the method in Application Example 1, and assembled into lithium-ion button half-cells.

[0109] Carry out charge and discharge test, the specific performance data is shown in Table 1.

[0110] Application Comparative Example 1

[0111] Preparation of negative electrode sheet:

[0112] Artificial graphite, conductive agent (carbon black) and binder (PVDF) in a mass ratio of 8:1:1 were mixed evenly and coated on the current collector. After vacuum drying at 60°C for 12 hours, the negative electrode sheets were cut.

[0113] The lithium ion button half-cell was assembled according to the method in Application Example 1, and the charge and discharge test was performed. The specific performance data is shown in Table 1.

[0114] Application Comparative Example 2

[0115] Preparation of negative electrode sheet:

[0116] Nano silicon powder (D50=50 nm), conductive agent (carbon black) and binder (PVDF) in a mass ratio of 8:1:1 were mixed evenly and coated on the current collector. After vacuum drying at 60°C for 12 hours, the negative electrode sheets were cut.

[0117] A lithium-ion button half-cell was assembled according to the method in Application Example 1, and a charge and discharge test was performed.

[0118] pass Figure 4 , 5 It can be seen that the first cycle charge and discharge capacity of the lithium-ion battery in this application comparison is good, reaching 2958.2 mAh g -1 、3315.9 mAh g -1However, the capacity retention rate after 50 cycles was 30.96%, which showed a significant decrease, indicating that the cycle stability was poor.

[0119] Specific performance data are shown in Table 1.

[0120] Application Comparative Examples 3~4

[0121] The sandwich-type silicon composite graphite negative electrode materials in Comparative Examples 1-2 were made into negative electrode sheets according to the method in Application Example 1, and assembled into lithium-ion button half-cells.

[0122] Carry out charge and discharge test, the specific performance data is shown in Table 1.

[0123] Table 1. Performance data of lithium-ion button half-cell

[0124]

[0125] According to Application Examples 1 to 4, the present invention significantly improves the electrical conductivity, energy density and cycle retention rate, and has good rate performance by loading hard carbon on a nanosilicon-graphite-nanosilicon structure substrate through carbonization, loading amorphous carbon by in-situ encapsulation through CVD, and partially filling the amorphous carbon in the pores of the hard carbon.

[0126] The lithium ion button half-cell prepared based on the sandwich-type silicon composite graphite negative electrode material in Application Example 1 of the present invention achieves both high energy density and good cycle retention rate compared to the lithium ion button half-cell based on artificial graphite and nano silicon powder in Application Comparative Examples 1 and 2.

[0127] In the carbonization process of Comparative Example 3, the dispersant is carbonized into hard carbon. When the hard carbon alone is used as the carbon layer, part of the nano-silicon powder directly contacts the electrolyte, resulting in a poor cycle retention rate. The performance of the negative electrode material obtained by extending the carbonization insulation time in Comparative Example 4 is not significantly improved compared with that in Comparative Example 3.

[0128] In summary, the present invention adopts a self-assembled composite structure, takes graphite as a support, uses hard carbon obtained by cracking a carbon source and amorphous carbon obtained by CVD to firmly adhere nano-silicon to the graphite surface, and the obtained sandwich-type silicon composite graphite negative electrode material effectively blocks the direct contact between the electrolyte and the nano-silicon powder; the assembled lithium-ion battery has good energy density and cycle retention rate.

[0129] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A sandwich-type silicon composite graphite negative electrode material, characterized in that: The sandwich-type silicon composite graphite negative electrode material uses a nano-silicon-graphite-nano-silicon structure as a substrate, and a carbon layer is loaded on the surface of the substrate, and the carbon layer includes hard carbon and amorphous carbon; the amorphous carbon is loaded on the outer surface of the hard carbon and filled in the pores of the hard carbon; The sandwich-type silicon composite graphite negative electrode material is prepared by the following steps: (1) First, add 300 g of polyvinyl pyrrolidone into 24 kg of anhydrous ethanol and wait for it to fully dissolve to obtain a dispersion; (2) Add 300 g of nano-silicon powder with a D50 of 50 nm to the dispersion, shear emulsify at 4200 rpm for 10 min, then add 2.4 kg of artificial graphite with a D50 of 8 μm, and shear emulsify at 4200 rpm for 20 min to obtain a uniformly dispersed suspension; (3) The suspension was spray dried, mechanical stirring was required during feeding, and a peristaltic pump was used for feeding at the same time. The spray drying temperature was 100 °C, the atomizing disk speed was 18000 rpm, the peristaltic pump feeding rate was 20 Hz, and the mechanical stirring rate was 200 rpm to obtain composite particles coated with a dispersant. (4) Placing the composite particles coated with the dispersant in a rotary kiln for carbonization under an inert gas, the rotary kiln speed is 20 rpm, the inert gas is argon, the flow rate is 500 sccm, the carbonization temperature is 900 °C, the heating rate is 10 °C / min, and the temperature is kept at 900 °C for 2 h and then cooled naturally to obtain a precursor; (5) The precursor was coated in situ by CVD, the CVD furnace speed was 10 rpm, the CVD temperature was 950 °C, 450 sccm of Ar, 350 sccm of C2H2, and 100 sccm of CH4 were introduced, the heating rate was 5 °C / min, and the temperature was kept for 2 h; a sandwich-type silicon composite graphite negative electrode material was obtained.

2. A negative electrode plate for a lithium-ion battery, characterized in that: The lithium-ion battery negative electrode plate comprises the sandwich-type silicon composite graphite negative electrode material according to claim 1.

3. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery negative electrode sheet according to claim 2.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode material, graphite-silicon-carbon composite material and preparation method

    CN117894965A